2004
DOI: 10.1021/bi049495l
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and Biochemical Analysis of Cocaine-Degrading Antibody 15A10,

Abstract: Catalytic antibody 15A10 hydrolyzes the benzoyl ester of cocaine to form the nonpsychoactive metabolites benzoic acid and ecgonine methylester. Here, we report biochemical and structural studies that characterize the catalytic mechanism. The crystal structure of the cocaine-hydrolyzing monoclonal antibody (mAb) 15A10 has been determined at 2.35 A resolution. The binding pocket is fairly shallow and mainly hydrophobic but with a cluster of three hydrogen-bond donating residues (TrpL96, AsnH33, and TyrH35). Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…Furthermore, the antibody affinity for cocaine should also be a major determinant of clinical efficacy. Unfortunately, the affinities of the catalytic mAb for cocaine were reported to be approximately 220 M (Larsen et al, 2004) and 55 to 5240 M (Matsushita et al, 2001), whereas the affinity of the anticocaine mAb GNC92H2 was reported to be 200 nM (Larsen et al, 2001). In contrast, the affinity of 2E2 for cocaine is approximately 4 nM (Paula et al, 2004), which is considerably higher than that of the other anticocaine mAb currently under study.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the antibody affinity for cocaine should also be a major determinant of clinical efficacy. Unfortunately, the affinities of the catalytic mAb for cocaine were reported to be approximately 220 M (Larsen et al, 2004) and 55 to 5240 M (Matsushita et al, 2001), whereas the affinity of the anticocaine mAb GNC92H2 was reported to be 200 nM (Larsen et al, 2001). In contrast, the affinity of 2E2 for cocaine is approximately 4 nM (Paula et al, 2004), which is considerably higher than that of the other anticocaine mAb currently under study.…”
mentioning
confidence: 97%
“…In addition to 2E2, Redwan et al (2003) have generated, characterized, and "humanized" the murine anticocaine mAb GNC92H2, the murine version of which has been shown to have in vivo efficacy in rat models of cocaine addiction (Carrera et al, 2001). In addition, two catalytic murine anticocaine mAb that are designed to reduce blood cocaine levels through its hydrolysis have been generated and characterized (Matsushita et al, 2001;Larsen et al, 2004). However, the murine catalytic mAb are likely to be immunogenic in humans.…”
mentioning
confidence: 99%
“…4, has been designed, synthesized, and used to successfully elicit anti-cocaine catalytic antibodies. 37 The new catalytic antibodies elicited by using TSA-3 so far are not more active than the previously discovered catalytic antibodies against cocaine. However, it might be interesting to test another possible TSA structure, i.e.…”
Section: Hydrolysis Of Boat Cocainementioning
confidence: 90%
“…Previously identified mAb 15A10 was converted to scFv format and mutants were examined; however, only relative kinetic data was reported. 55 Antibodies 3F5 and 3H9 represent novel anticocaine catalytic antibodies. Although they are 89% homologous, antibody 3F5 is twice as active as antibody 3H9.…”
Section: Discussionmentioning
confidence: 99%